Analysis of early childhood occupational therapy intervention in a group of clients with low graphomotor skills - Kováčová, Barbora; Lištiaková, Ivana (Journal of Exceptional People, 2017)
Early childhood occupational therapy is considered a comprehensive form of help, which is provided for children with risk development, children with potentially risk development and children with specific disabilities within the systems of their families. The presented paper comprises of the analysis of an occupational therapy intervention, a specifically constructed programme of occupational therapy that was designed for clients at the age of 5 to 6 with low graphomotor skills. In the methodological part of the article, the authors present statistically significant differences in data before and after the realization of the occupational therapy programme. As part of the verification we chose two standardized tests: the first one used was F-test, then Student’s t-test comparing the means of two samples during pre- and post- assessment testing. Drawing from the analysis of the results of the long-term occupational therapy intervention, it can be stated that the conducted programme is useful and meaningful as it was proven by the factors of comparison in the test and re-rest.
Keywords: postižení; Occupational Therapy; Exercise; psychomotorické poruchy; Psychomotor Disorders; hodnotící studie jako téma; Persons with Disabilities; Child; cvičení; dítě; Motor Skills Disorders; poruchy motorických dovedností; Humans; lidé; ergoterapie; Evaluation Studies as Topic